Israel : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2006)
This 2005 Article IV Consultation highlights that following a strong performance in 2004, Israel's economic expansion accelerated in 2005, supported by a relatively favorable global economic environment, an improvement in the security situation, and prudent policies. Real GDP grew at an estimated 5.2 percent in 2005. Inflation is slightly higher than a year ago, but remains in check. The unemployment rate continues to fall, but remains high. The macroeconomic policies and structural reforms of recent years have opened up the economy, increased its competitiveness, and attracted foreign investment.